Assessment of fertility potential index of some soils of Moheshkhali betel leaf (Piper betle L.) estate (Journal of Biodiversity Conservation and Bioresource Management, 2022)
Fifteen soil samples (0-15cm depth) and fifteen betel leaf samples from Bara Moheshkhali, Choto Moheshkhali, Hoanak, Kalmarchora, Shaplapur union of Moheshkhali upazila, Cox’s Bazar district were collected on December-January (2020-2021). It was collected for the purpose of evaluating the color, particle density, moisture content, texture, pH, EC and organic matter content of soils and total nitrogen, phosphorous, potassium and sulfur of the soils and total protein content, nitrogen, phosphorus, potassium and sulfur of leaves. Maximum sampled soil was containing yellowish red color when moist and showed brown color when dried. Some of them were flood plain soil and that’s why showed grey color during dry and moist condition. Mean particle density was 2.49 g/cm3 and mean moisture content was 13.95%. Average sand, silt and clay were 65.08%, 18.56% and 19.26%, respectively. The texture of the soils was sandy loam to clay loam. The sand was by far the dominant fraction in the soils. Mean pH value was 5.63, organic matter was 0.30% and EC was 99.38μS/cm. Mean total nitrogen, phosphorus, potassium and sulfur of the soils were 0.04, 0.46, 0.25 and 0.26%, respectively. The mean concentration of protein, nitrogen, phosphorus, potassium and sulfur in the betel leaf samples were 20.56, 3.29, 0.39, 0.79 and 0.20%, respectively. This investigation focuses on the fertility status and physico-chemical properties of soil in betel leaf garden of only hilly island of Bangladesh, Moheshkhali.J. Biodivers. Conserv. Bioresour. Manag. 2021, 7(1): 25-32